PARTICULARITIES OF THE DEVELOPMENT OF THE PAREMIUM FUND IN AZERBAIJANI AND OTHER TURKISH LANGUAGES - Gasilova, L.H (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article analyzes the linguistic and cultural basis of the concepts "proverb", "proverb", "phraseology" in a comparative historical and comparative typological plane. It is determined that in order to identify their place within other genres, it is necessary to take into account their syntactic, semantic and pragmatic characteristics. The research results give reason to say that the Azerbaijani paremias are Turkic, among which there are numerous examples of coincidences, which proves the kinship of the linguistic and folklore culture of the eastern and western Turkic ethnic groups. The level of language perception, the specificity of memory, the level of synonyms used in speech and the possibility of using euphemisms play a big role here. In the modern period of historical development, many paremias acquire new meanings and forms in connection with the impact of new language slangs that have arisen in social networks, as well as a diverse combination of bilingualism. An important role here is played by social communication between native speakers. So, there is interaction and mutual influence between different Turkic languages, in connection with close contacts between the peoples of these countries. At the same time, one should not forget modern language processes when the role of international languages is growing.